Peningkatan Prestasi Belajar Fisika Dengan Media Laboratorium Virtual PhET Pokok Bahasan Listrik Dinamis - ., Subkannayla (Inovasi: Jurnal Diklat Keagamaan, 2020)
Student-centered learning strategies and creating a pleasant atmosphere are needed to improve student learning outcomes in physics, the subject of dynamic electricity. PhET Virtual Laboratory Media is expected to increase student activity in the teaching and learning process because students will be involved physically, emotionally and intellectually, which in turn is expected that the concepts taught by the teacher can be understood by students. While the objectives of this study are: (a) To determine the improvement of student achievement with the Virtual PhET (Physics Educational Technology) Laboratory Media. (b) To determine the effect of student motivation with PhET Virtual Laboratory Media (Physics Educational Technology). This study uses action research in two cycles. Each cycle consists of four stages, namely: Planning, Activity (action), Observation (Observation) and Reflection. The target of this research is the students of Class XII IPA-3 MAN 2 Mojokerto. The data obtained are in the form of formative test results, observation sheets of teaching and learning activities. From the results of the analysis, it was found that the student's learning achievement had increased from cycle 1 to cycle 2, namely, cycle 1 was 59.37%, and cycle 2 became 87.5%. In the second cycle, classical student learning completeness was achieved. The conclusion of this study is that learning with PhET Virtual Laboratory Media can have a positive effect on student achievement and learning motivation in class XII IPA-3 MAN 2 Mojokerto for the 2019/2020 academic year, and this learning model can be used as an alternative to learning physics on the subject of dynamic electricity.